2019
DOI: 10.1029/2019wr025094
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Low Instream Large Wood Retention and Imprints of Wood Mobility in Mountain Nonperennial Streams of a Mediterranean Semiarid Environment

Abstract: The majority of research on instream large wood (LW) focuses on perennial streams in temperate zones, and much less is known about wood distribution and its driving factors in other environments, such as semiarid bioclimatic regions. In this study, we sought to predict LW retention by assessing reach‐scale variables to infer the influence of external factors on the presence of LW in 37 independent reaches of ephemeral and intermittent streams draining a mountain range in a Mediterranean semiarid environment (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Despite the frequent flood events of high magnitudes causing significant damages on infrastructure and fatalities (six floods in the period 1993−2016; Karaouzas et al, 2017), overall low in‐channel and floodplain LW volumes likely prevented the effective clustering of transported LW into jams. The same relation between low LW volumes and low frequency of jams was previously reported from non‐perennial steep channels in Crete (Galia et al, 2019) or semi‐arid glaciogenic basins of the Rocky Mountains (Scott & Wohl, 2018) with these observations suggesting low biomass productivity of riparian corridors in semi‐arid conditions in relation to LW recruitment.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Despite the frequent flood events of high magnitudes causing significant damages on infrastructure and fatalities (six floods in the period 1993−2016; Karaouzas et al, 2017), overall low in‐channel and floodplain LW volumes likely prevented the effective clustering of transported LW into jams. The same relation between low LW volumes and low frequency of jams was previously reported from non‐perennial steep channels in Crete (Galia et al, 2019) or semi‐arid glaciogenic basins of the Rocky Mountains (Scott & Wohl, 2018) with these observations suggesting low biomass productivity of riparian corridors in semi‐arid conditions in relation to LW recruitment.…”
Section: Discussionsupporting
confidence: 82%
“…Our analyses confirmed our first hypothesis on the impact of flow intermittency, together with characteristics of riparian stands, on LW loads in the fluvial corridor. At a global scale, previous reports have indicated a decrease in in‐channel LW volumes at increasing channel width and catchment area (Gurnell et al, 2002; Ruiz‐Villanueva et al, 2016; Wohl, 2017), with similar results reported in the Mediterranean region, (in steep non‐perennial streams of Crete, Greece; Galia et al, 2019). In the case of the studied intermittent river, we found no inverse correlation between in‐channel LW retention (represented by LW frequency per stream length and LW volume per channel area) and channel width (4.8–37.7 m) or catchment area (36–1775 km 2 ).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations